FORMULATION AND EVALUATION OF FAST DISINTEGRATING TABLET OF PROPRANOLOL HYDROCHLORIDE USING MODIFIED TAMARIND SEED GUM AS A NATURAL SUPERDISINTEGRANT - Rani, Nisha; DEV, DHRUV (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study was carried out for the preparation of modified Tamarindus indica seed gum as a natural superdisintegrant and assessed various parameters for preparing a fast disintegrating dosage form. Methods: The extracted gum from tamarind seeds was chemically modified by the carboxymethylation method. Then, calcium complexation of carboxymethyled tamarind seed gum was done. Fast disintegrating tablets were prepared by the direct compression method. The change in the functional groups of the extracted gum, Carboxymethyl tamarind seed gum, and the calcium complexed tamarind seed gum was studied by FT-IR spectrophotometer. DSC studies of calcium complexed tamarind seed gum showed alterations in the melting point without undergoing any modification. Results: The pre-formulation studies such as physical appearance, swelling index, and viscosity of calcium complexed tamarind seed gum were characterized. From the studies, it was concluded that modified Tamarind seed gum was acidic and hydrophilic. The pH of the extracted tamarind seed gum was found to be 5.4. The fast disintegrating tablets were evaluated for hardness, friability, disintegration time, thickness, and in-vitro dissolution study. In the present study, the disintegration time of calcium complexed tamarind seed gum-containing tablets was compared with the marketed formulation of croscarmellose sodium as a synthetic superdisintegrant. The F5 formulation of calcium complexed tamarind seed gum showed a disintegration time of 37±2 s whereas the marketed formulation of croscarmellose sodium showed a disintegration time of 48±2 s. Conclusion: It can be concluded that a fast disintegrating tablet prepared using calcium complexed Tamarind seed gum improves the disintegration time of the tablet.